2017
DOI: 10.1037/abn0000228
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neural responses to feedback in depressed adolescents.

Abstract: Depression rates surge in adolescence, particularly among females. Recent findings suggest that depressed adolescents are characterized by hypersensitivity to negative outcomes and blunted responsiveness to rewards. However, our understanding of the pathophysiology and time course of these abnormalities remains limited. Due to their high temporal resolution, event-related potentials (ERPs) provide an ideal probe to investigate these processes. In the present study, healthy (n = 25) and depressed (n = 26) femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 83 publications
10
48
0
1
Order By: Relevance
“…examining the effect of an acute psychosocial stressor on a sensitive measure of neural processing of rewards, the RewP, and its associated spectral characteristics, and by examining potential buffering effects of increased neural response to reward on HPA axis response to the stressor. This study replicated previous work showing that delta power is specifically enhanced following reward-related feedback (Bernat et al, 2015;Bernat et al, 2011;Bowers et al, 2018;Webb et al, 2017), and further demonstrated that the previously identified reduction in rewardrelated neural activity following stress (e.g., Berghorst et al, 2013;Casement et al, 2014;Ethridge et al, 2018;Ossewaarde et al, 2011;Porcelli et al, 2012;Treadway, Buckholtz, & Zald, 2013) was specific to neural activity in the delta frequency. Lastly, this study demonstrated that baseline reward sensitivity in the delta frequency was associated with a reduced cortisol response to a subsequent stressor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…examining the effect of an acute psychosocial stressor on a sensitive measure of neural processing of rewards, the RewP, and its associated spectral characteristics, and by examining potential buffering effects of increased neural response to reward on HPA axis response to the stressor. This study replicated previous work showing that delta power is specifically enhanced following reward-related feedback (Bernat et al, 2015;Bernat et al, 2011;Bowers et al, 2018;Webb et al, 2017), and further demonstrated that the previously identified reduction in rewardrelated neural activity following stress (e.g., Berghorst et al, 2013;Casement et al, 2014;Ethridge et al, 2018;Ossewaarde et al, 2011;Porcelli et al, 2012;Treadway, Buckholtz, & Zald, 2013) was specific to neural activity in the delta frequency. Lastly, this study demonstrated that baseline reward sensitivity in the delta frequency was associated with a reduced cortisol response to a subsequent stressor.…”
Section: Discussionsupporting
confidence: 89%
“…Neural activity occurring in the time window of the RewP is thought to be composed of both delta frequency (~1-4 Hz) and theta frequency (~4-8 Hz) activity. Evidence suggests that delta power is increased following rewards, or positive outcomes, compared to losses or negative outcomes, whereas theta power appears specifically enhanced following non-rewards, or negative outcomes (Banis et al, 2014;Bernat, Nelson, & Baskin-Sommers, 2015;Bernat, Nelson, Steele, Gehring, & Patrick, 2011;Bowers, Buzzell, Bernat, Fox, & Barker, 2018;Cohen, Elger, & Ranganath, 2007;Foti et al, 2015;Van de Vijver, Ridderinkhof, & Cohen, 2011;Webb et al, 2017). Additionally, findings from source analyses indicate that delta and theta activity may have distinct neural generators: gain-related delta has been localized to the striatum, while loss-related theta activity has been localized to the anterior cingulate cortex (Foti et al, 2015).…”
Section: Acute Stress and Rewardmentioning
confidence: 99%
“…Next, within the time-frequency domain, we observed that theta power was increased for losses compared to gains, and delta power was increased for gains compared to losses. These time-frequency effects for feedback are consistent with previous adolescent (Nelson et al, 2017; Webb et al, 2017) and adult (Bernat et al, 2011; Foti et al, 2015) samples. Similarly, inter-trial phase synchrony (ITPS) within theta was increased for losses compared to gains, while delta ITPS was increased for gains relative to losses.…”
Section: Discussionsupporting
confidence: 89%
“…Theta power is typically increased for losses compared to gains; whereas, delta power is typically increased for gains compared to losses (Bernat et al, 2011; Cohen, 2007; Foti et al, 2015; Nelson et al, 2017; van de Vijver, Ridderinkhof, & Cohen, 2011; Webb et al, 2017). Theories of the functional significance of loss-related theta suggest that theta acts as a signal that recruits subsequent increased attention or top-down control following salient events like errors, novel stimuli, or negative feedback (Aviyente, Tootell, & Bernat, 2017; Cavanagh & Frank, 2014; Cavanagh, Zambrano-Vazquez, & Allen, 2012; Van Noordt, Campopiano, & Segalowitz, 2016; van Noordt, Desjardins, Gogo, Tekok-Kilic, & Segalowitz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They were from universities located near the Institute of Psychology Chinese Academy of Sciences, such as Beijing Forestry University and China Agricultural University. We determined the sample size based on two considerations: (1) How many participants were usually involved in previous between-group ERP studies (e.g., Li et al, 2015;Pintzinger, Pfabigan, Pfau, Kryspin-Exner, & Lamm, 2017;Webb et al, 2017), and (2) how many participants are needed to ensure 80% statistical power to detect a small-to-medium effect size (Vazire, 2016). Accordingly, we invited 50 college students to participate in the experiment.…”
Section: Participantsmentioning
confidence: 99%